Entrepreneurship research in the Poland. Issue 3 (4th May 2017) - Czemiel-Grzybowska, Wioletta; Skowronek-Mielczarek, Anna
Abstract: Access to financing plays an eminent role for a small enterprise sector in any economy. Research usually finds a positive size efficiency relationship, but few studies focus on sectors dominated by small and medium-sized firms (SMEs). This paper fills this gap by analyzing this relationship in the Polish industry sector, which is both successful and increasingly dominated by SMEs. It is envisaged that this study will contribute to the existing literature on small enterprise financing, with an emphasis on financial constraints in the Polish small enterprise industry sector. The paper presents only part of research. Analysis of the data will present an insight into the actual barriers for small enterprises constraints associated with debt financing arrangements.